Identification of Primary Initiation Sites for DNA Replication in the Hamster Dihydrofolate Reductase Gene Initiation Zone - Kobayashi, Takehiko (American Society for Microbiology, 1998)
Mammalian replication origins appear paradoxical. While some studies conclude that initiation occurs bidirectionally from specific loci, others conclude that initiation occurs at many sites distributed throughout large DNA regions. To clarify this issue, the relative number of early replication bubbles was determined at 26 sites in a 110-kb locus containing the dihydrofolate reductase (DHFR)-encoding gene in CHO cells; 19 sites were located within an 11-kb sequence containing ori-β. The ratio of ∼0.8-kb nascent DNA strands to nonreplicated DNA at each site was quantified by competitive PCR. Nascent DNA was defined either as DNA that was labeled by incorporation of bromodeoxyuridine in vivo or as RNA-primed DNA that was resistant to λ-exonuclease. Two primary initiation sites were identified within the 12-kb region, where two-dimensional gel electrophoresis previously detected a high frequency of replication bubbles. A sharp peak of nascent DNA occurred at the ori-β origin of bidirectional replication where initiation events were 12 times more frequent than at distal sequences. A second peak occurred 5 kb downstream at a previously unrecognized origin (ori-β′). Thus, the DHFR gene initiation zone contains at least three primary initiation sites (ori-β, ori-β′, and ori-γ), suggesting that initiation zones in mammals, like those in fission yeast, consist of multiple replication origins.